2019
DOI: 10.7341/20191519
|View full text |Cite
|
Sign up to set email alerts
|

Socio-Economic Requirements as a Fundament of Innovation in Food Packaging

Abstract: The food packaging industry trends refl ect the identi fi ed needs and requirements of consumers because entrepreneurs should sati sfy changing consumer requirements to achieve and maintain a competi ti ve advantage due to innovati on. In the group of socioeconomic needs, the most important ones are lifestyle changes, improving the quality of life through the added value off ered to consumers through packaged products, profi table companies in the sector, packaged product safety and environmental protecti on. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…The primary goal of the field of information science is to examine consumer attitudes and behaviors toward food packaging, and then analyze the results to determine what the most important features of packaging are for consumers, which are comfort for use and durability [12]. In regard to socioeconomic needs, the very distinguished ones are lifestyle changes, in a way that reflects the quality of life through the added value offered to consumers through packaged products, profitable companies, packaged product safety, and environmental protection [13].…”
Section: Food Packaging Science and Emerging Trendsmentioning
confidence: 99%
“…The primary goal of the field of information science is to examine consumer attitudes and behaviors toward food packaging, and then analyze the results to determine what the most important features of packaging are for consumers, which are comfort for use and durability [12]. In regard to socioeconomic needs, the very distinguished ones are lifestyle changes, in a way that reflects the quality of life through the added value offered to consumers through packaged products, profitable companies, packaged product safety, and environmental protection [13].…”
Section: Food Packaging Science and Emerging Trendsmentioning
confidence: 99%
“…Nevertheless, one can still notice a low level of the ecological awareness of society, manifested in a lack of knowledge concerning basic issues, such as the proper separation of packaging waste, the need for cleaning it before disposal and understanding designations placed on packaging. On the other hand, popular demands for environmental protection and reducing a negative impact on the environment in the context of packaging have been already seen for years (Cholewa-Kawecka, Ingrao, Siracusa, 2019). The foregoing shows clearly that effective ecological education supporting the achievement of objectives resulting from EU membership should be also a vital component of the Polish extended producer responsibility system.…”
Section: Raising Society's Ecological Awareness Of Packaging Placed O...mentioning
confidence: 99%
“…One of the indicators of food safety is its packaging. Research provided in Poland found the safety of packaging was the most critical socio-economic need for consumers (Cholewa-Wójcik et al, 2019). Analyzing attitudes towards organic foods in Sweden, Magnusson et al (2001) determined that it was difficult for consumers to distinguish between product labels: some consumers did not distinguish between labels for organic vs. conventional food.…”
Section: Consumer Behavior Regarding Organic Productsmentioning
confidence: 99%
“…In addition, a study by Irianto (2015) showed that different genders' consumer intentions also differed in their buying behavior regarding organic product: females were more conscious towards health and environment than males. The impact of consumers' age on their perception of product packaging's safety was detected in the research provided by Cholewa-Wójcik et al (2019): consumers aged between 26-35 years and 36-45 years considered the safety of product packaging as being important. The respondents represented mainly urban women samples.…”
Section: Consumer Behavior Regarding Organic Productsmentioning
confidence: 99%